Spatio-temporal variation in sediment ecosystem processes and roles of key biota in the Scheldt estuary. (30th June 2019) - Fang, Xiaoyu; Mestdagh, Sebastiaan; Ysebaert, Tom; Moens, Tom; Soetaert, Karline; Van Colen, Carl
Abstract: Bioturbation (i.e. particle reworking and bio-irrigation) is a key process in benthic coastal and estuarine ecosystems, and act as crucial control on important ecosystem functions, such as nutrient cycling. Particle reworking and bio-irrigation are affected by a wide array of environmental and biological factors and are therefore expected to be highly variable in heterogeneous ecosystems, such as estuaries. To assess the spatial and temporal variability of these benthic ecosystem processes in the Scheldt estuary (Belgium and the Netherlands), we carried out seasonal surveys during four seasons in 2015 and 2016, at three habitats with different hydrodynamic regimes (low-dynamic intertidal, high-dynamic intertidal, subtidal) in the three main salinity zones (polyhaline, mesohaline, oligohaline). Sediment communities were sampled and incubated in the laboratory; macrobenthos was identified and weighed. Luminophore tracers were applied to the incubation cores to measure sediment particle mixing and changes over time in the concentration of the inert tracer sodium bromide in the water column were used to estimate pore water exchange rate as a proxy for bio-irrigation. Particle reworking was quantified both by the rate of mixing, and the maximal penetration depth of luminophores. Luminophore profiles showed that biodiffusion was the dominant particle reworking mode. Both particle reworking and bio-irrigation were highly variable among seasons and habitats, and different species were found to contribute unevenly to both processes, and between habitats and seasons. Habitat structuring effects on populations, density-dependent interactions with the habitat, and temperature-driven variability in macrobenthos activity and living position are suggested to explain the observed spatial and temporal differences. Graphical abstract: Image 1 Highlights: Particle reworking and bio-irrigation in the Scheldt vary strongly in space and time. Biodiffusion is the dominant particle reworking mode across habitats and seasons. Macrofauna species contribution to both ecosystem processes vary in space and time.